PENINGKATAN KEAKTIFAN SISWA MELALUI INTEGRASI POWERPOINT INTERAKTIF DAN GAME EDUKATIF DALAM PEMBELAJARAN BIOLOGI DAN MATEMATIKA - Cheriani; Naila Maharani, Andi; Lira Virna, Andi; Nurafifah; Az Zahra, Rahma; Nabil Salsah, Aditya; Aristan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the integration of educational technology through the use of PowerPoint media and educational games in biology and mathematics learning to improve student activeness. The background of this research is based on the low level of student participation in learning processes that are still dominated by conventional teaching methods. This study employed a quantitative approach with a quasi-experimental design involving students as research subjects. Data were collected using observation sheets and assessments of student activeness during the learning process. The results indicate that the use of interactive learning media in the form of PowerPoint combined with game-based evaluation significantly improves student activeness, as shown by increased participation, interaction, and student responses during learning activities. In addition, the integration of educational technology creates a more engaging and enjoyable learning environment, which enhances students’ learning motivation. Therefore, the integration of educational technology in biology and mathematics learning is considered an effective alternative strategy to improve student activeness in schools.